GENESIS 1:26-28 A PANACEA TO ENVIRONMENTAL DEGRADATION IN NIGER DELTA, NIGERIA - Finomo Julia, Awajiusuk (Asian Horizons, 2012)
Whether the cornucopians (those who argue against imminent threat to human life by environmental pollution) or their cautious optimistic (those who hold that with good management the resources of the earth can take care of all humanity) allies accept it or not there is a serious threat to the continued existence of the earth. This results largely from the reckless exploitation of the earth’s resources which has in turn culminated into environmental degradation. Experts warn that, if measures are not taken and urgently too, humans and other occupants of the environment stand the risk of total destruction. In the Niger Delta, various forms of environmental degradation are prevalent and with far reaching negative impacts. This is occasioned by the discovery of oil at Oloibiri in 1956. Before this discovery, the natives were polluting the environment but at a minimal level.